THE INFLUENCE OF SOCIAL MEDIA USE ON PERSONALITY AND STUDENT LEARNING DISCIPLINE - Juma, Nuraida Oktaviani (Universitas Lambung Mangkurat, 2024)
With the advancement of information technology, the use of the internet, particularly social media, has become increasingly widespread. This has raised concerns about its impact on students' personalities and learning discipline. This study aims to explore the influence of social media usage on the personality and learning discipline of students at STKIP PGRI Sukabumi. The research employs a quantitative method with a simple linear regression approach, involving 100 student respondents. The two main variables analyzed are social media usage, personality, and learning discipline. Instrument testing was conducted for validity and reliability, followed by simple linear regression analysis. The results indicate a significant influence of social media usage on students' personalities and learning discipline. These findings are expected to provide insights for educators and educational institutions in utilizing social media constructively in the teaching and learning process.